Development Of Hydrocolloids-Coated Noodles For Enhanced Salt Release In The Mouth - Yeoh, Shin Yong (2022)
Yellow alkaline noodles (YAN) with low-salt content pose low textural and mechanical properties. Consequently, they collapse easily in overall structure upon cooking, i.e. become soft, soggy, and crumble into smaller pieces. In addition to this major setback, low salt content in YAN impairs the taste and saltines perception by the consumers. Furthermore, Commercial YAN have a very short shelf life (up to 2 days), even under refrigeration storage. This study aims to develop zero-salted YAN coated with using of high amylose corn starch HylonVIITM (HC) or a mixture of sucrose esters of fatty acids and carboxymethyl cellulose SemperfreshTM (SC). The noodles is hypothesised to have the same (or better) shelf life, textural, mechanical, and sensory properties, as well as able to enhance salt release in the mouth than YAN.